An efficient electrocatalyst as cathode material for solid oxide fuel cells: BaFe0·95Sn0·05O3−δ - Dong, F.; Ni, M.; He, W.; Chen, Y.; Yang, G.; Chen, D.; Shao, Zongping (Elsevier SA, 2016)
The B-site substitution with the minor amount of tin in BaFeO3−δ parent oxide is expected to stabilize a single perovskite lattice structure. In this study, a composition of BaFe0·95Sn0·05O3−δ (BFS) as a new cathode material for intermediate-temperature solid oxide fuel cells (IT-SOFCs) is synthesized and characterized. Special attention is paid to the exploration of some basic properties including phase structure, oxygen non-stoichiometry, electrical conductivity, oxygen bulk diffusion coefficient, and surface exchange coefficient, which are of significant importance to the electrochemical activity of cathode materials. BFS holds a single cubic perovskite structure over temperature range of cell operation, determined by in-situ X-ray diffraction and scanning transmission electron microscope. A high oxygen vacancy concentration at cell operating temperatures is observed by combining thermo-gravimetric data and iodometric titration result. Furthermore, electrical conductivity relaxation measurement illustrates the fast oxygen bulk diffusion and surface exchange kinetics. Accordingly, testing cells based on BFS cathode material demonstrate the low polarization resistance of 0.033 Ω cm2 and high peak power density of 1033 mW cm−2 at 700 °C, as well as a relatively stable long-term operation for ∼300 h. The results obtained suggest that BFS perovskite oxide holds a great promise as an oxygen reduction electrocatalyst for IT-SOFCs.